ANALISIS KADAR MANGAN (Mn) PADA AIR ALKALI DENGAN MENGGUNAKANSPEKTROFOTOMETER SERAPAN ATOM (SSA) - Andi Auliyah Warsyidah; Jurnal Syarif; Cahyaning Abdullah (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2019)
A Research about analysis of manganese (Mn) levels in alkaline water using an atomic absorption spectrophotometer (SSA) was carried out from 16-18 August 2017 in the laboratory of energy and mineral resources services. The purpose of this research are 1) to find out whether there is a manganese substance (Mn) in alkaline water, 2) to determine how much manganese (Mn) levels in alkaline water. Quantitative research methods with experimental types where the entire population taken in this research alkaline water traded in Makassar City. Samples in this study were 3 types of alkaline water with different brands, samples were taken using random sampling techniques. Each sample was measured 50 mL after adding 5 mL of concentrated HNO3. The results showed that the levels of manganese (Mn) from 3 different types of alkaline water brands for sample A were 0.030 mg / L, sample B was 0.060 mg / L, and sample C was 0.050 mg / L.